2007
DOI: 10.2460/javma.230.5.690
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasonographic appearance of lesions and cytologic and histologic diagnoses in splenic aspirates from dogs and cats: 32 cases (2002–2005)

Abstract: Ultrasound-guided aspiration of splenic lesions is a minimally invasive tool for obtaining specimens for cytologic evaluation. Although cytologic diagnoses often reflect histologic results, if missampling or incomplete sampling occurs or tissue architecture is required to distinguish between reactive and neoplastic conditions, accurate diagnosis with fine-needle aspiration may not be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 22 publications
3
105
1
4
Order By: Relevance
“…Além disso, causa desconforto mínimo ao paciente, permitindo que se realizem múltiplas colheitas e amostragens em série, particularmente interessantes quando surgem resultados inconclusivos ou quando existe suspeita de recidiva da lesão 21 . No homem e no cão cada vez mais há estudos que empregam a PAAF para o diagnóstico deste tipo de neoplasia 4,22,23,24,25 . Nos casos de linfadenomegalia, este exame permite a diferenciação rápida entre processos reacionais benignos e neoplásicos 26 .…”
Section: Introductionunclassified
“…Além disso, causa desconforto mínimo ao paciente, permitindo que se realizem múltiplas colheitas e amostragens em série, particularmente interessantes quando surgem resultados inconclusivos ou quando existe suspeita de recidiva da lesão 21 . No homem e no cão cada vez mais há estudos que empregam a PAAF para o diagnóstico deste tipo de neoplasia 4,22,23,24,25 . Nos casos de linfadenomegalia, este exame permite a diferenciação rápida entre processos reacionais benignos e neoplásicos 26 .…”
Section: Introductionunclassified
“…Survey studies of splenic diseases in this species have reported a prevalence of splenitis ranging from 0.9% to 8%. 7,20 Among its causes, splenitis was described in only single case reports associated with fungal, 2,5,14,25,34,45,46,52 protozoan, 3,18,29,39 or bacterial 1,2,6,12,17,31,40,42,48 infections.The cases related to fungal infections invariably had poor prognosis. In these dogs, necropsy identified splenomegaly and multiple foci of necrosis, while histology documented pyogranulomatous inflammation, multinucleated giant cells, and, in some cases, fungal hyphae.…”
mentioning
confidence: 97%
“…Although this rare tumour showed divergent phenotypic differentiation in this study, the surgery contributed to prolong survival and there was no evidence of tumour infiltration or metastases during the 9-month follow-up period. Sonographic evidence of multiple nodular splenic changes is often associated with malignancy, but is not specific for any particular disease (Hanson et al 2001;Ballegeer et al 2007). Mesenchymomas represent 4% of all splenic malignancies (Spangler and Kass 1997); however, the relative size and morphological appearance makes it difficult to differentiate malignant mesenchymomas from other mesenchymal tumours (Johnson et al 1989;Spangler et al 1994).…”
Section: Discussionmentioning
confidence: 99%